Holding Her Own : The Exceptional Life of Jackie Ormes - Todd, Traci N.; Wright, Shannon (Illustrator) (New York : Orchard Books, an imprint of Scholastic Inc., 2023)
"When Jackie Ormes sees an opportunity, she takes it. She's a journalist, cartoonist, fashionista, philanthropist, and activist -- and she wants to use her artistry to bring joy and hope to Black people everywhere. But in post-World War II America, Black people are still being denied their civil rights, and Jackie has a dilemma: How can her art remain true to her signature Jackie joy, while also staying honest about the inequalities Black people have been fighting against? Traci N. Todd and Shannon Wright have crafted a gorgeous and moving tribute to the indelible legacy of America's first Black woman cartoonist"--
Keywords: Ormes, Jackie, -- 1911-1985 -- Juvenile literature; Ormes, Jackie, -- 1911-1985.; Cartoonists -- Biography -- United States; African American women cartoonists -- Biography; Cartoonists; African Americans -- Biography; Women -- Biography